Effects of aspirin in combination with EPA and DHA on HDL-C cholesterol and ApoA1 exchange in individuals with type 2 diabetes mellitus. (November 2017) - Block, Robert C.; Holub, Ashley; Abdolahi, Amir; Tu, Xin M.; Mousa, Shaker A.; Oda, Michael N.
Abstract: Background/synopsis: Low-dose aspirin is an effective drug for the prevention of cardiovascular disease (CVD) events but individuals with diabetes mellitus can be subject to 'aspirin resistance'. Thus, aspirin's effect in these individuals is controversial. Higher blood levels of seafood-derived omega-3 polyunsaturated fatty acids (ω3) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) also have beneficial effects in reducing risk of CVD events but few studies have examined the interaction of plasma EPA and DHA with aspirin ingestion. Objective/purpose: Our study examined the combinatory effects of EPA, DHA, and aspirin ingestion on HDL-cholesterol (HDL-C) and apoA-I exchange (shown to be associated with CVD event risk). Methods: 30 adults with Type 2 diabetes mellitus ingested aspirin (81 mg/day) for 7 consecutive days, EPA+DHA (2.6 g/day) for 28 days, then both for 7 days. Plasma was collected at baseline and at 5 subsequent visits including 4 h after each aspirin ingestion. Mixed model methods were used to determine HDL-C-concentrations and apoA-I exchange compared to the baseline visit values. LOWESS curves were used for non-linear analyses of outcomes to help discern change patterns, which was followed by piecewise linear functions for formal testing of curvilinear relationships. Results: Significant changes (p < 0.05) compared to baseline in both HDL-C-concentrations and apoA-I exchange were present at different times. After 7 days of aspirin-only ingestion, apoA-I exchange was significantly modified by increasing levels of DHA concentration, with increased apoA-I exchange observed up until log(DHA) of 4.6 and decreased exchange thereafter (p = 0.03). These LOWESS curve effects were not observed for EPA or HDL-C (p > 0.05). Aspirin's effects on apoA-I exchange were the greatest when EPA or DHA concentrations were moderate compared to high or low. Comparison of EPA, DHA, and EPA+DHA LOWESS curves, demonstrated that the majority of the effect is due to DHA. Conclusion: Our results strongly suggest that plasma concentrations of EPA and DHA influence aspirin effects on lipid mediators of CVD event risk where their concentrations are most beneficial when moderate, not high or low. These effects on HDL-C cholesterol and apoA-I exchange are novel. Personalized dosing of DHA in those who take aspirin may be a beneficial option for patients with type 2 diabetes mellitus. Highlights: This study highlights the effects of aspirin on HDL cholesterol and apoAI exchange. These effects are enhanced when plasma DHA is moderate. The statistical approach included the use of a locally weighted LOWESS curve. When V-shaped relationships were apparent, piecewise linear regression followed. A precision medicine approach taking fatty acid effects into account is warranted.